2017
DOI: 10.1111/psyp.13009
|View full text |Cite
|
Sign up to set email alerts
|

Affective priming and cognitive load: Event‐related potentials suggest an interplay of implicit affect misattribution and strategic inhibition

Abstract: Prior research suggests that the affective priming effect denoting prime-congruent evaluative judgments about neutral targets preceded by affective primes increases when the primes are processed less deeply. This has been taken as evidence for greater affect misattribution. However, no study so far has combined an experimental manipulation of the depth of prime processing with the benefits of ERPs. Forty-seven participants made like/dislike responses about Korean ideographs following 800-ms affective prime wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
2
11
0
1
Order By: Relevance
“…Another component indicating resource allocation is centro-parietal N400 (Kutas & Hillyard, 1980). Indeed, in Gibbons et al (2018), N400 for was specifically increased for negative (irrelevant) prime words in an evaluative priming task, which we interpreted as a negativity bias. N400 tended to be larger for negative than neutral words also in Herbert et al (2008), and was significantly reduced for positive words.…”
Section: The Present Approachmentioning
confidence: 77%
“…Another component indicating resource allocation is centro-parietal N400 (Kutas & Hillyard, 1980). Indeed, in Gibbons et al (2018), N400 for was specifically increased for negative (irrelevant) prime words in an evaluative priming task, which we interpreted as a negativity bias. N400 tended to be larger for negative than neutral words also in Herbert et al (2008), and was significantly reduced for positive words.…”
Section: The Present Approachmentioning
confidence: 77%
“…Facilitated processing (reaction times) is showed in affectively congruent targets and impaired processing is showed in incongruent ones, a phenomenon known as the affective priming effect. The presentation of priming stimuli can automatically activate the related emotional representations of the brain and carry out implicit emotional processing [46,47]. Multiple studies have shown the priming effect, and this effect can be also detected using ERP data [45,48,49].…”
Section: Emotion Induced By Moral Violations Influence Subsequent Promentioning
confidence: 99%
“…Moreover, as shown in the affective priming literature, emotion at retrieval can serve as context for the information that is retrieved, causing it to be interpreted in an emotion-consistent fashion (e.g. Bower & Forgas, 2001; Forgas, 2008; Gibbons, Seib-Pfeifer, Koppelheie-Gossel, & Schnuerch, 2018).…”
Section: Problematic Investigatory Tools: the Case Of Feti (Forensic ...mentioning
confidence: 99%